PENGARUH INTERVENSI PELATIHAN TERHADAP PENINGKATAN KOMPETENSI KARYAWAN: SEBUAH REVIEW LITERATUR - Farah Syaufika; Febrina Pinkan; Muhammad Farid Alifianto; Netty Merdiaty (CV. ADIBA AISHA AMIRA, 2025)
Amidst the increasingly fierce global competition, human resource management (HRM) has become an important component in enhancing employee competence to support organizational performance. By analyzing ten journal articles, this research investigates the impact of training interventions on employee competence. The research results show that training improves employees' knowledge, skills, and attitudes. The methods used, the relevance of the material, and the quality of the trainers are all factors that influence the quality of the training. Training has also been proven to enhance employees' ability to adapt to changes, accelerate the achievement of company goals, and help them develop their own careers. One of the main recommendations is the structured measurement of training outcomes and aligning training programs with the needs of the organization and employees. According to the research findings, well-planned training is a strategic investment that helps the company succeed.